Effects of Bile Acids and Lipase Supplementation in Low-Energy Diets on Growth Performance, Fat Digestibility and Meat Quality in Broiler Chickens - Arshad,MA (2020)
ABSTRACT The aim of this study was to investigate the effect of bile acids and lipase supplementation in low energy (LE) diets on growth, fat digestibility, serum lipid profile and meat quality of broilers. Seven hundred one-day-old broiler chicks were divided into 5 dietary treatments with five replicates of 28 birds each. The five treatments were: i) high energy diet (HE; metabolizable energy (ME) = 3,000 and 3,170 kcal/kg for starter and finisher diet), ii) low energy diet (LE; ME = 2,900 and 3,070 kcal/kg for starter and finisher diet), iii) LE diet supplemented with 300 g/ton bile acids (LEB), iv) LE diet supplemented with 180 g/ton lipase (LEL), v) LE diet supplemented both with bile acids (300 g/ton) and lipase (180 g/ton). The experiment lasted 35 days having starter phase from days 1-21 and finisher phase from days 22-35. Dietary inclusion of both bile acids and lipase in LE diet had no effect (p>0.05) on body weight (BW) gain and feed intake. High energy diet reduced feed intake and BW gain during starter and overall period; however, during finisher phase BW gain was similar in all dietary treatments. Dietary energy level had no effect on feed conversion ratio. Fat digestibility (p>0.05) both in the starter and finisher phase was not affected by the dietary treatments. Concentration of total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol and triglycerides were not affected by the dietary treatments (p>0.05). Meat quality of breast and thigh muscle was unaffected due to the dietary treatments (p>0.05). It is concluded that the supplementation of bile acids alone or in combination with lipase in low-energy diets did not improve broiler performance, fat digestibility, serum lipid profile and meat quality.